1998
DOI: 10.1177/074823379801400115
|View full text |Cite
|
Sign up to set email alerts
|

A Physiologically Based Approach To the Study of Bisphenol a and Other Estrogenic Chemicals On the Size of Reproductive Organs, Daily Sperm Production, and Behavior

Abstract: Two chemicals previously shown to have estrogenic activity, bisphenol A and octylphenol, were examined for their effects on accessory reproductive organs and daily sperm production in male offspring of mice fed these chemicals during pregnancy. These chemicals are used in the manufacture of plastics and other products, and have been detected in food and water consumed by animals and people. From gestation day 11-17 female mice were fed an average concentration (dissolved in oil) of bisphenol A or octylphenol o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
356
7
6

Year Published

1999
1999
2008
2008

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 714 publications
(389 citation statements)
references
References 52 publications
13
356
7
6
Order By: Relevance
“…In males the slight changes observed point to an effect of prenatal BPA in inducing more defensive-type strategies during agonistic encounters and in slowing the copulatory sequence, but we also observed a reduction of sexual performance in postnatally treated animals. On the whole, in both sexes, sexual activity seems quite sensitive to perinatal exposure to BPA, in line with recent research showing significant effects on behavior and on reproductive indices after early BPA administration (9,10,18,19). The direction of the observed modifications in the two sexes in our experiment suggests that the effect of early BPA exposure on adult behavior may not be mediated by a classic organizational process activated by estrogenic action.…”
Section: Discussionsupporting
confidence: 75%
“…In males the slight changes observed point to an effect of prenatal BPA in inducing more defensive-type strategies during agonistic encounters and in slowing the copulatory sequence, but we also observed a reduction of sexual performance in postnatally treated animals. On the whole, in both sexes, sexual activity seems quite sensitive to perinatal exposure to BPA, in line with recent research showing significant effects on behavior and on reproductive indices after early BPA administration (9,10,18,19). The direction of the observed modifications in the two sexes in our experiment suggests that the effect of early BPA exposure on adult behavior may not be mediated by a classic organizational process activated by estrogenic action.…”
Section: Discussionsupporting
confidence: 75%
“…Nagel et al (1997) have described exposure of pregnant CF 1 mice to BPA (2, 20 µg/kg/ day) during GD 11-17 to result in an increase in prostate weights of mature pups. vom Saal et al (1998) further reported reduced sperm efficiency in a subset of offspring exposed to BPA during pregnancy, for which enlarged prostates had been observed. However, Ashby and Tinwell (1998) argued that there were experimental deficiencies in their work.…”
Section: Discussionmentioning
confidence: 99%
“…Experiments demonstrating that minuscule amounts of parent BPA alter the reproductive organs of developing mice recently sparked the greatest alarm concerning this substance. Exposure of rodent fetuses to BPA at a very low dose (below the no-observed-adverse-effect level) typical of environmental exposure was found to produce postnatal estrogenic effects: reduced daily sperm production in males, increased prostate gland weight, alteration in the development and tissue organization of the mammary gland, disruption of sexual differentiation in the brain, long-term deleterious effects in the vagina, and accelerated growth and puberty in females (Howdeshell et al 1999;Kubo et al 2001;Markey et al 2001;Nagel et al 1997;Schonfelder et al 2002;Talsness et al 2000;vom Saal et al 1998;Welshons et al 1999). Some groups, however, were unable to reproduce the effects on the reproductive tract (Ashby et al 1999;Cagen et al 1999aCagen et al , 1999b, leading to a controversial discussion of their potentially harmful effects.…”
mentioning
confidence: 99%